PROFILING JUNIOR HIGH SCHOOL STUDENT'S CRITICAL-THINKING SKILL ON LEARNING SPEED IN CAMBRIDGE CURRICULUM - Diana Ayu Latifah, - (2021)
The curriculum, which plays a significant role in the education system, particularly in the teaching and learning process, is one factor that impacts the effectiveness of education. This study of profiling the students' critical thinking in Cambridge curriculum implementation of speed topic aimed to investigate students' critical thinking ability in implementing the Cambridge curriculum in learning speed. Convenience sampling was used as the method to collect the data. The participants were 33 7th grade junior high school students in one of the private schools in Bandung which implement the Cambridge curriculum. The result shows that students' critical thinking ability indicates a low level with an average percentage score of 50,5%, and the highest percentage of critical thinking indicator is Inference 57,70%. The lower percentage score is Basic Support 41,91%. Other indicators are Elementary Clarification with the score percentage is 51,47%, Advanced Clarification 45,58%, and Strategic and Tactics 55,88%. Based on the research, the possibility of students' critical thinking cases is categorized as low because of the lack of time duration in-class learning, which causes limited class activities. One of the effects is the absence of interaction between students in class. The absence of activities that require them to work together makes the students lack the ability to explore and solve the problem which trains students' critical thinking.